PEMBERDAYAAN CAREGIVER MELALUI PELATIHAN TERAPI MUSIK KLASIK UNTUK MENDUKUNG REHABILITASI ORANG DENGAN GANGGUAN JIWA BERBASIS KOMUNITAS - Okti Rahayu Asih; Desty Lismayanti; Yanti Rosmiyanti; Sumitro Sumitro; Sarini Sarini; Gia Fadillah Lutfi (Bajang Institute, 2025)
People with Mental Disorders (PMDs), particularly individuals with schizophrenia, require continuous rehabilitation to improve their functional abilities, social interactions, and overall quality of life. In community-based mental health services, caregivers play a crucial role in providing daily support and ensuring continuity of care at home. However, many caregivers have limited knowledge and practical skills regarding non-pharmacological interventions that can enhance the rehabilitation process. Classical music therapy is a simple, safe, and cost-effective complementary intervention that has been reported to promote relaxation, reduce anxiety, improve emotional stability, and enhance social functioning among individuals with mental disorders. This community service program aimed to strengthen caregivers' knowledge and practical skills in implementing classical music therapy as part of community-based rehabilitation for people with mental disorders. The program employed a Participatory Learning and Action (PLA) approach involving 30 caregivers through health education, demonstrations, hands-on practice, simulations, and continuous mentoring. Program effectiveness was evaluated using pretest–posttest assessments and observational checklists to measure participants' knowledge and competency in conducting classical music therapy sessions at home. The results demonstrated a significant improvement in caregivers' understanding of the principles of music therapy, appropriate music selection, therapy duration, and effective patient assistance during therapy sessions. Furthermore, caregivers reported increased confidence in managing patients' emotional responses, establishing positive communication, and encouraging greater participation in daily rehabilitation activities. The implementation of classical music therapy also strengthened caregivers' involvement in the recovery process and promoted a more supportive home environment for individuals with mental disorders. This community empowerment program indicates that classical music therapy training is a practical, sustainable, and low-cost strategy for enhancing caregivers' capacity and supporting community-based mental health rehabilitation. Integrating this intervention into community mental health programs is expected to improve the quality of life of people with mental disorders, strengthen family participation, and promote comprehensive and person-centered mental healthcare services.